Virtual Reconstruction Method of Regional 3D Image Based on Visual Transmission Effect. (12th June 2021) - Yin, Jing; Yang, Jong Hoon
Abstract : In order to solve the problems of poor user experience and low human-computer interaction efficiency, this paper designs a 3D image virtual reconstruction system based on visual communication effects. First, the functional framework diagram and hardware structure diagram of the image 3D reconstruction system are given. Then, combined with the basic theory of visual communication design, the characteristics of different elements in the three-dimensional image system and reasonable visual communication forms are analyzed, and design principles are proposed to improve user experience and communication efficiency. After the input image is preprocessed by median filtering, a three-dimensional reconstruction algorithm based on the image sequence is used to perform a three-dimensional reconstruction of the preprocessed image. The performance of the designed system was tested in a comparison form. We optimize the original hardware structure, expand the clock module, and use the chip to improve the data processing efficiency; in the two-dimensional image; we read the main information, through data conversion, display it in three-dimensional form, select the feature area, extract the image feature, calculate the key physical coordinate points, complete the main code compilation, use visual communication technology to feed back the display visual elements to the 3D image, and complete the design of the 3D image virtual reconstruction system. The test results showed that the application of visual communication technology to the virtual reconstruction of 3D images can effectively remove noise and make the edge area of the image clear, which can meet the needs of users compared with the reconstruction results of the original system. Visual C ++ and 3DMAX are used as the system design platform, and three-dimensional image visualization and roaming are realized through OpenGL. Experimental results show that the designed system has better reconstruction accuracy and user satisfaction.